1993
DOI: 10.1002/eji.1830230919
|View full text |Cite
|
Sign up to set email alerts
|

The B7 adhesion molecule is expressed on activated human T cells: Functional involvement in T‐T cell interactions

Abstract: The B cell antigen B7 delivers a strong co-stimulatory signal for the activation of T cells by binding to its ligands CD28 and CTLA4. Here we demonstrate the surface expression of the B7 molecule on activated human T cells in vitro and under certain conditions in vivo and its functional importance in T-T cell interactions. B7 was detected by flow cytometry on antigen-specific CD4+ and allospecific CD8+ cloned T cells from different donors with anti-B7 monoclonal antibody (mAb) or a soluble CTLA4-C gamma 1 chim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 32 publications
(27 reference statements)
3
49
0
Order By: Relevance
“…A previous study by Azuma et al (17) demonstrated that T cell clones coexpress both CD28 and CD80 simultaneously. Similarly, studies by Wyss-Coray et al (34) demonstrated that cloned T cells activated with APCs and rested for various times express CD80 at 7-9 days postactivation. However, it should be pointed out that these T cells were stimulated in the presence of APCs for long period of times.…”
Section: Discussionmentioning
confidence: 80%
“…A previous study by Azuma et al (17) demonstrated that T cell clones coexpress both CD28 and CD80 simultaneously. Similarly, studies by Wyss-Coray et al (34) demonstrated that cloned T cells activated with APCs and rested for various times express CD80 at 7-9 days postactivation. However, it should be pointed out that these T cells were stimulated in the presence of APCs for long period of times.…”
Section: Discussionmentioning
confidence: 80%
“…Yet other studies have implicated various costimulatory molecule receptors, such as OX-40 (13,14), ICOS (15), and CD28 (16)(17)(18)(19), in the differential development of Th2 over Th1 cells. Although costimulation is typically considered to be delivered to a T cell by an APC, functional interactions between T cells via costimulatory molecules and their receptors have been described (20); this is especially true for CD28 and the CD80/86 costimulatory molecules (21)(22)(23)(24). Ag dose is also known to affect the Th1/Th2 phenotype of the ensuing response.…”
mentioning
confidence: 99%
“…is another mechanism by which CD80/CD86 expression is regulated (21,24,39,43,46,54). For instance, T lymphocytes activated through CD3/CD28 will express both CD80 and CD86 (4,14,48,56). Thus, it will be interesting to investigate the possible relationships between the types of producer cells in which HIV-1 is expanded (e.g., CD4 ϩ T cells versus macrophages), the types of stimuli used to activate virus producer cells, and the degree of incorporation of CD80 and CD86 into mature HIV-1 particles.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient incorporation of CD80 and CD86 in clinical isolates of HIV-1 produced by cytokine-treated macrophages. As specified above, the two most important cellular reservoirs of HIV-1, i.e., monocytes/macrophages and CD4 ϩ T lymphocytes, can also express both CD80 and CD86 (3,4,14,24,25,48,56). Since CD80 and CD86 are upregulated after the treatment of cells of the monocytic lineage with cytokines (reviewed in reference 28), we finally studied the process of CD80 and CD86 incorporation in field isolates of HIV-1 bearing distinct coreceptor utilization profiles (i.e., R5 and X4).…”
Section: Fig 3 the Infectivity Of Cd80-and Cd86-bearing Hiv-1 Viriomentioning
confidence: 97%
See 1 more Smart Citation